Issues Faced by Elementary School Students in Solving Problem-Solving Questions in Mathematics - Nurhaswinda Nurhaswinda; Siska kartika Ningsih; Eka Nur Hidayanti; Nadia Anggraini; Rizky Indah Mutiara; Alya Mukhbita; Tresia Agustina Sitompul; Naila AZ Zahra; Mega Lefina Natania; Indra Saputra (The Future of Education Journal, 2025)
This study aims to examine the various issues faced by elementary school (SD) students in solving problem-solving tasks in mathematics through a literature review approach. Problem-solving is one of the essential skills in mathematics learning, closely linked to higher-order thinking abilities. However, several research findings indicate that many elementary school students struggle to understand and solve problem-solving tasks. This study collects and analyzes various literature sources, including national journals, scientific articles, and relevant reference books. The findings reveal that common issues faced by students include: (1) insufficient understanding of basic mathematical concepts, (2) difficulties in reading and understanding word problems, (3) limitations in formulating problem-solving strategies, and (4) lack of reflection and evaluation skills regarding the obtained answers. In addition to the internal factors of students, external aspects such as less contextual teaching approaches, limited use of engaging learning media, and insufficient support from the learning environment also contribute to these problems. This study recommends strengthening a systematic and adaptive problem-solving-based learning approach from an early age to enhance students' critical thinking abilities in mathematics.